Gênese da educação de surdos em Delmiro Gouveia - Vilela, Cristiano das Neves (2016)
The purpose of this research is to investigate the genesis of deaf education in Delmiro Gouveia, state of Alagoas. This is a historical research based on the assumptions of Cultural History and Identity and Cultural Studies and covers a time frame between 1981 and 2005. Delmiro Gouveia is a city with a unique industrial history and inherited its name from the pioneer in the energy production with São Francisco river waters. Also, by its geographical location in the state's limits, this is the farthest city from the capital and where, consequently, the Brazilian Sign Language (Libras) took longer to be known. We seek to discuss the issue of deafness in the Brazilian sertão based on the first institution to meet deaf in the extreme sertão of Alagoas: the Association of Parents and Friends of Exceptional People (APAE) of Delmiro Gouveia, founded in 1981. Data collection was conducted based on documentary research and semi-structured interviews with deaf people, their parents and teachers. We analyze their practices and track which representations about the deaf and deafness were usually constructed and accepted. We showed the actors who participated in the deaf schooling, how they learned Libras in the sertão and how the particular language needs of deaf people were seen in their families and institutional environment. We concluded that activities in APAE did not meet the linguistic and educational needs of the deaf students; that Libras' introduction in Delmiro Gouveia occurred in 1998 through the social worker Elias; and that social representations about deaf people in the observed period relate to the stereotypes associated with a medicalized view of deafness and legitimized speeches that considered deaf people as disabled, aggressive, inefficient and hampered by being born in the sertão. Thus, we intend to contribute to the educational history of the deaf in Alagoas and in the Brazilian Northeast, which is still lacking this kind of investigation.